ABSORPTION OF MODERATION VALUE IN THE FATWA FLEXIBILITY; CASE ON HANDLING A COVID-19 CORPSE - Muammar Bakry; Abdul Syatar; Muhammad Majdy Amiruddin; M. Ilham (istinbath, 2021)
This article aims to analyze and provide ideas about the absorption of moderation values to those who are competent. Fatwa is flexible. Fatwas must have moderate dimensions. This article uses a philosophical approach by analyzing literature, both in the form of classic literature, books, journals and other sources. This article provides the idea that absorption of Fatwas is moderated by balancing all aspects. It is neither hard nor loose. Such a style of Fatwa can be seen from the results of the decided Fatwa that remains in the corridor of the Shari’a, weighs greater consideration, matches the reality of the needs of Muslims, and provides equal convenience. Fatwa must become barometer controlling changes in social reality for Muslims. Every emerging legal issue is responded quickly and accurately. However, what needs to be considered is the method used in exploring the laws related to contemporary problems according to the Fatwa procedure and all its consequences. The implications of the study indicatea that the absorption of moderate Fatwa are things that should get attention, both among laity and competent mufti. Mufti is demanded to produce Fatwa that can be accepted by Muslims but does not neglect religious texts originating from Allah. and the Messenger of Allah. Mufti must adopt policies regarding the problems faced by Muslims today. The moderate Fatwa aims to prevent Muslims from carrying out legal arbitrarily and in accordance with their own passions